1996
DOI: 10.1074/jbc.271.23.13882
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Thrombin Anion-binding Exosites 1 and 2 in the Activation of Factor V and Factor VIII

Abstract: The role of anion-binding exosites of thrombin in the activation of factor V and factor VIII was studied using thrombin Arg93 --> Ala, Arg97 --> Ala, and Arg101 --> Ala (thrombin RA), a recombinant exosite 2 defective mutant, and a synthetic N-acetylated dodecapeptide, Ac-Asn-Gly-Asp-Phe-Glu-Glu-Ile-Pro-Glu-Glu-Tyr-O-SO4Leu (hirugen), which competitively inhibits binding of macromolecules to exosite 1. The catalytic efficiency of the activation of factor VIII or of the first step of factor V activation by thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
157
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 64 publications
8
157
0
1
Order By: Relevance
“…This latter observation was based upon results showing that mutations at Arg-740, impairing this cleavage, significantly reduced cleavage rates at the two other P1 sites. Thrombin-catalyzed activation of factor VIII is dependent upon interactions involving the anion binding exosites of the proteinase (11,12). Exosite binding is believed to determine substrate affinity, whereas subsequent active site docking primarily affects V max (13).…”
mentioning
confidence: 99%
“…This latter observation was based upon results showing that mutations at Arg-740, impairing this cleavage, significantly reduced cleavage rates at the two other P1 sites. Thrombin-catalyzed activation of factor VIII is dependent upon interactions involving the anion binding exosites of the proteinase (11,12). Exosite binding is believed to determine substrate affinity, whereas subsequent active site docking primarily affects V max (13).…”
mentioning
confidence: 99%
“…Whereas ABE-I has been involved in the binding to thrombomodulin (40), fibrinogen (41), PAR1 (42), the COOH-terminal hirudin peptides (43), and heparin cofactor II (44) among others, ABE-II was found to be involved in the interaction with protease nexin (45) and antithrombin III (44). Data from separate laboratories have demonstrated that both exosites bind factors V and VIII (33,34,35). Interestingly, proexosite I of prothrombin, which is present at a low affinity state on the molecule, and its affinity for its ligands increases by ϳ100-fold following activation and formation of thrombin (33,39), was found to be directly involved in the productive interaction with factor Va within prothrombinase (32,33).…”
mentioning
confidence: 99%
“…The critical roles of exosites I and II in regulation of macromolecular interactions of thrombin are well established (12,13), including the role of exosite I in fibrinogen substrate recognition (14,15), and both exosites in thrombomodulin-regulated protein C activation (16 -18), factor V (19 -22), and factor VIII (19) activation. In addition, exosite II binds heparin (23), regulating inactivation of thrombin by antithrombin (24), and Pro fragment 2 (F2, 25).…”
mentioning
confidence: 99%